The Effect of Using Pair Check and Snowball Throwing Learning Models on Students' Problem Solving Ability - Juliana Dwi Maulidiya (Universitas Islam Jember, 2020)
The research abaut the effect of the use of the pair check and snowball throwing learning model on problem solving abilities was carried out with the aim of recognizing the influence of the use of the model on problem solving abilities. The research was conducted in SMP 06 Diponegoro with 27 respondents in VIII A and 30 students in VIII B who were taken with the Purposive Sampling technique. This type of research is a true-experimental research with a Posttest-Only Control Design and uses a quantitative approach. The method taken in this research is test and documentation. The data analysis that used is normality test, homogeneity test, and t test (Independent T Test) with the help of SPSS software version 20.0. Based on the research results obtained p-value 0.02 < 0.05 then Ha is accepted and Ho is rejected. Thus it can be said that there is an effect on the use of the pair check and snowball throwing learning model on students' problem solving abilities Keywords: pair check, snowball throwing, problem solving skills